The spatial autocorrelation analysis for transport accessibility in selected regions of the European Union - Joanna Górniak (Comparative Economic Research. Central and Eastern Europe, 2016)
In view of the significant differences between the socio-economic regions, the level of development of transport is not homogenous. According to Tobler's law (1970) we can point out that all objects are related to each other, but the ones located closer are more dependent on each other than those farther away. Then we can identify the occurrence of spatial autocorrelation. For example, the European regions can assess whether the border regions of different countries show a similarity to each other. The main purpose of this article is to assess and analyze the occurrence of spatial autocorrelation in connection with the transport accessibility (measured by density of a motorway network). The general hypothesis is: between European regions, there is a positive spatial autocorrelation in connection with the problems of transport accessibility. Research subjects are selected European regions at NUTS level 2. To evaluate the occurrence of spatial autocorrelation the classic Moran I statistic has been used.
Keywords: 330; spatial autocorrelation; transport accessibility; Moran's I statistic